The Language of Digital Text and Its Creative Elements: A Reading of Textual Structure and Aesthetic Dimensions - Baadji, Ismahane (LANGUAGE ART, 2025)
This research examines the concept of digital text and its linguistic/structural characteristics, offering a comprehensive vision of this new form of literary creativity. It highlights features that distinguish digital texts from traditional ones, such as their interactive structure and dynamic language shaped by digital interfaces. The study also analyzes the creative process, explaining how digital media transform text production/reception and introduce new aesthetic dimensions to the reading experience. Furthermore, the paper reviews key definitions of digital text proposed by scholars, exploring diverse perspectives to deconstruct the concept. It discusses how traditional literary theories have been compelled to rethink core notions like text, author, and reader due to rapid technological advancements, which have spurred new modes of literary communication and reader interaction. The research also investigates the relationship between digital text and reception aesthetics, demonstrating how interactive media redefine the reader’s role—from a passive consumer to an active co-creator of the text. Finally, it addresses critical challenges, including: Preserving textual authenticity, Evolving authorship/reception dynamics, And theoretical gaps in analyzing this literary form.